2022
DOI: 10.3390/healthcare10050896
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence Rate of SARS-CoV-2 Infection in Health Care Workers at a Dedicated COVID-19 Hospital: Experiences of the Pandemic from a Large Mexican Hospital

Abstract: Health care workers (HCW) are at high risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The incidence of SARS-CoV-2 infection in HCW has been examined in cross-sectional studies by quantitative polymerase chain reaction (qPCR) tests, which may lead to underestimating exact incidence rates. We thus investigated the incidence of SARS-CoV-2 infection in a group of HCW at a dedicated coronavirus disease 2019 (COVID-19) hospital in a six-month follow-up period. We conducted a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The incidence of COVID-19 in HCWs may mirror the prevalent community environment and local epidemiology [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Additional occupational exposure of HCWs has been postulated to be a significant risk factor for acquisition of SARS-CoV-2 in some settings [ 10 , 11 , 12 , 13 , 14 ]. Maintaining protection of HCWs through appropriate infection control methods and vaccination remains critical to maintaining a public health and clinical care workforce in order to manage the pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of COVID-19 in HCWs may mirror the prevalent community environment and local epidemiology [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Additional occupational exposure of HCWs has been postulated to be a significant risk factor for acquisition of SARS-CoV-2 in some settings [ 10 , 11 , 12 , 13 , 14 ]. Maintaining protection of HCWs through appropriate infection control methods and vaccination remains critical to maintaining a public health and clinical care workforce in order to manage the pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only volunteers with no previous diagnosis or symptoms of SARS-Cov-2 were considered. A detailed account of the cohort constitution with criteria related to the selection of participants, clinical evaluation of volunteers and chemical laboratory analysis protocols is presented in [18] . Here we summarize the main cohort procedure considerations: (i) All participants had medical examinations both physical and clinical.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent publication, we reported on results of a cohort of healthcare workers (HCW) from the Hospital General de México Dr. Eduardo Liceaga (HGMEL), who were exposed during the early phase of the COVID-19 pandemic in Mexico, from August to December 2020 [ 1 ]. The cohort underwent a baseline evaluation during which a variety of categorical and continuous variables were registered, including medical history, demographic, anthropomorphic, clinical and laboratory information, and working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…No additional information was recorded for the hypertensive participants (e.g., the degree of hypertension), but all hypertensive participants were medicated and had blood pressure measurements in the range normal to normal-high, indicating that their hypertensive condition was under control. We concluded that it is possible that participants recognizing themselves as a vulnerable population with comorbidities, such as hypertension, followed safety procedures and social distancing more strictly than participants without known comorbidities, and therefore by adapting their behavior were less likely to become infected [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation